Blockchain for the arts, music and artistic research - Łukawski, Adam; Music, AI and Blockchain: Decentralized Creativity and Posthuman Agency (doctoral focus session) Orpheus Instituut, Gent December 18-19, 2023; Orpheus Instituut (Ghent, Belgium) (Ghent Orpheus Instituut, 2023)
The goal of this focus session was to equip participants with an understanding of how AI and blockchain technologies are changing society, and how they can augment and redefine creative processes in music. The session explored the potential of several digital tools for posthuman creative practices, providing insights into emergent modes of artistic creation. More specifically, the session addressed topics such as the enhancement of human creativity through AI, effective techniques for investigating music with AI and blockchain, the significance of concepts such as decentralized creativity, posthuman music, hypermusic, Music 2.0, and the role and ownership of art in the posthuman era. Meetings involved theoretical discussions and practical hands-on experience, such as examples of composing with AI models or creating music NFTs.The lecture "Blockchain for the arts, music and artistic research" introduced blockchain technology as a new medium and artistic tool in the context of artistic research. It introduced topics such as decentralisation, the technicalities of blockchain technology, various types of blockchain, Non-fungible tokens (NFTs), Decentralised Autonomous Organisations, Generative Music NFTs, the concept of on-chain purity and the concept of Decentralised Creative Networks.
FRIS
0
Keywords: MetamusicX:Transdisciplinary Encounters in and Beyond Music